Small Crocodyliform from the Lower Cretaceous (Late Aptian) of Central Texas and its Systematic Relationship to the Evolution of Eusuchia. (September 2014) - Adams, Thomas L.
Abstract : A new Early Cretaceous neosuchian crocodyliform is recognized on the basis of two skulls and postcranial material collected from the late Aptian Twin Mountains Formation at Proctor Lake, central Texas. The new species, Wannchampsus kirpachi, is distinguished by a unique combination of characters including an enlarged third maxillary tooth, internal choanae bordered anteriorly by the palatines and by the pterygoids posteriorly and laterally, anterior margin of the choanae situated at the posterior edge of the suborbital fenestrae, a median crest along the midline of the parietal and frontal, and procoelous vertebrae. A phylogenetic analysis recovered the new taxon as the sister to the 'Glen Rose form, ' an undescribed taxon of neosuchian. Together, with Shamosuchus, Batrachomimus, and Rugosuchus, they form a monophyletic group, Paralligatoridae, that is the sister clade to Eusuchia within Neosuchia. The Proctor Lake taxon and the undescribed yet widely discussed 'Glen Rose form' are referable to the same genus.